2018
DOI: 10.4103/ijccm.ijccm_31_18
|View full text |Cite
|
Sign up to set email alerts
|

Speech and swallowing function outcome following early tracheostomy in patients who underwent neurosurgical intervention

Abstract: Background:Evaluation of late-onset speech and swallowing complications of tracheostomy on neurotrauma cases, as the most common intensive care unit procedure, needs to be evaluated.Objectives:A prospective study conducted in a tertiary care teaching hospital to find the late-onset speech and swallowing complications of tracheostomy in neurotrauma cases.Materials and Methods:This prospective observational study was conducted in the intensive care unit on intubated patients needing elective tracheostomy at a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Research groups reported early tracheostomy reduced number of ICU days though in critically ill patients, death would not be caused by tracheostomy alone. Mortality rate in ICU reduced in early tracheostomy cases contrary to some studies [8]. Other published literatures also reported the same observations on tracheostomy [9].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Research groups reported early tracheostomy reduced number of ICU days though in critically ill patients, death would not be caused by tracheostomy alone. Mortality rate in ICU reduced in early tracheostomy cases contrary to some studies [8]. Other published literatures also reported the same observations on tracheostomy [9].…”
Section: Discussionsupporting
confidence: 52%
“…In cases of excessive secretions in very severe head injury, when it took prolonged decannulation and hospital stay with financial constraints of patients, the domiciliary caregivers were provided adequate training in tracheostomy as well as nursing care. Further, they were asked to procure a small foot operated or electric suction apparatus with capacity building in sucking off the excess pooled secretions before the patient were discharged [8]. An Egyptian study reported that there were significantly longer durations of ICU stay in tracheostomized patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest, the article by Kumar et al . [ 1 ] titled “Speech and Swallowing Function Outcome Following Early Tracheostomy in Patients Who Underwent Neurosurgical Intervention.” We appreciate this article along with the limitations highlighted by the authors. Swallowing dysfunction is not very uncommon after endotracheal intubation and is observed in nearly 20% patients who suffered from acute respiratory failure.…”
mentioning
confidence: 99%